Enduring Cancer Life, Death, and Diagnosis in Delhi - Banerjee, Dwaipayan (Critical Global Health: Evidence, Efficacy, Ethnography, 2020)
Dwaipayan Banerjee explores the efforts of Delhi's urban poor to create a livable life with cancer as they negotiate an over-extended health system unequipped to respond to the disease.